1883 Mo. Laws 76, Concealed Weapons, § 1 - (:unkn) unknown (General Publisher, 1883)
Prohibited the carrying of a concealed fire arms, Bowie knife, dirk, dagger, slungshot, or other deadly weapon to a church, school, election site, or other public setting or carrying in a threatening manner or while intoxicated. Punishable by fine of $25-200 and/or by imprisonment up to 6 months.
--
Keywords: CARRY - CONCEALED